The Pattern of Cardiac Arrhythmias in Acute ST Elevated Myocardial Infarction and their in-hospital Outcome - Alam, Mohammad Khurshadul; Mahmood, Manzoor; Adhikary, Dipal Krishna; Khaled, Fakhrul Islam; Chowdhury, Msi Tipu; Hasan, Amanat; Islam, Sami Nazrul; Sultan, Md Ashraf Uddin; Banerjee, Sajal Krishna (University Heart Journal, 2020)
Background: Acute myocardial infarction (AMI) is a major cause of death worldwide with arrhythmia being the most common determinant in the post-infarction period. Identification and management of arrhythmias at an early period of acute MI has both short term and long term significance. Objective: The aim of the study is to evaluate the pattern of arrhythmias in acute STEMI in the first 48 hours of hospitalization and their inhospital outcome. Methods: A total of 50 patients with acute STEMI were included in the study after considering the inclusion and exclusion criteria. The patients were observed for the first 48 hours of hospitalization for detection of arrhythmia with baseline ECG at admission and continuous cardiac monitoring in the CCU. The pattern of the arrhythmias during this period & their in-hospital outcome were recorded in predesigned structured data collection sheet. Result: The mean age was 53.38 ± 10.22 years ranging from 29 to 70 years. Most of the patients were male 42(84%). Majority of the patients had anterior wall ( anterior, antero-septal & extensive anterior) myocardial infarction (54%). Sinus tachycardia in isolation was the most common arrhythmia observed in 36.8% of patients followed by sinus bradycardia (22.8%), ventricular tachycardia (19.3%), ventricular ectopic (12.3%),first degree AV block (5.3%), complete heart block and atrial ectopic 1.7% each. Tachyarrhythmias were more common in anterior wall myocardial infarction, whereas bradyarrhythmias were more common in inferior wall myocardial infarction. Among studied patients, 72% had favourable outcome , followed by acute left ventricular failure 10%, cardiogenic shock & lengthening of hospital stay 8% each and death 2%. Conclusion: The commonest arrhythmias encountered were sinus tachycardia followed by sinus bradycardia, ventricular tachycardia, ventricular ectopic, AV block and atrial ectopic. The incidence of mortality was 2%. University Heart Journal Vol. 16, No. 1, Jan 2020; 16-21